From the Bottom Up: Developing a Literacy Practitioner Research Network in British Columbia - Audrey Thomas; Diane Morrison; Sandy Middleton; Marina Niks; Tom Nesbit; Ralf St.Clair (Adult Education Research Conference, 2000)
This roundtable will address the developments and challenges involved in building research capacity among literacy practitioners in the province of British Columbia through collaborative partnerships between various agencies. Case examples of different approaches will be presented with opportunities for questions and discussion.